Incidence and risk factors predisposing anastomotic leak after transhiatal esophagectomy - Tabatabai, Abbas (Medknow Publications, 2009)
OBJECTIVE: The objective of our study was to identify the incidence and risk factors of anastomotic leaks following transhiatal esophagectomy (THE). MATERIALS AND METHODS: A prospective study was conducted on 61 patients treated for carcinoma of the esophagus between 2006 and 2007. We examined the following variables: age, gender, preoperative cardiovascular function, intraoperative complications such as hypotension, arrhythmia, mediastinal manipulation period, blood loss volume, blood transfusion, duration of surgery, postoperative complications such as anastomotic leak, anastomotic stricture, requiring reoperation, respiratory complications, and total morbidity and mortality. Variables were compared between the patients with and without anastomotic leak. T-test for quantitative variables and Chi-square test for qualitative variables were used to find out any relationship. P value less than 0.05 was considered significant. RESULTS: Out of 61 patients, anastomotic leaks occurred in 13 (21.3%). Weight loss, forced expiratory volume (FEV1) <2 lit, preoperative albumin, intaoperative blood loss volume, and respiratory complication were associated with the anastomotic leak in patients undergoing THE. Anastomotic leaks were the leading cause of postoperative morbidity, anastomotic stricture, and reoperation. CONCLUSION: Anastomotic leakage is a life-threatening postoperative complication. Careful attention to the factors contributing to the development of a leak can reduce the incidence of anastomotic complications postoperatively.